Database protection model based on security system with full overlap - Vilihura, V.V.; Yesin, V.I. (Radiotekhnika, 2021)
Security is one of the most important characteristics of the quality of information systems in general and databases, as their main component, in particular. Therefore, the presence of an information protection system, as a complex of software, technical, cryptographic, organizational and other methods, means and measures that ensure the integrity, confidentiality, authenticity and availability of information in conditions of exposure to natural or artificial threats, is an integral feature of almost any modern information system and database. At the same time, in order to be able to verify the conclusions about the degree of security, it must be measured in some way. The paper considers a database security model based on a full overlap security model (a covered security system), which is traditionally considered the basis for a formal description of security systems. Thanks to expanding the Clements-Hoffman model by including a set of vulnerabilities (as a separately objectively existing category necessary to describe a weakness of an asset or control that can be exploited by one or more threats), which makes it possible to assess more adequately the likelihood of an unwanted incident (threat realization) in a two-factor model (in which one of the factors reflects the motivational component of the threat, and the second takes into account the existing vulnerabilities); a defined integral indicator of database security (as a value inverse to the total residual risk, the constituent components of which are represented in the form of the corresponding linguistic variables); the developed technique for assessing the main components of security barriers and the security of the database as a whole, based on the theory of fuzzy sets and risk, it becomes possible to use the developed model to conduct a quantitative assessment of the security of the analyzed database.